High Hepatitis B Seroprevalence, Low Knowledge, and Poor Attitude towards Hepatitis B Virus Infection among Market Women in Bolgatanga Metropolis in the Upper East Region of Ghana - Gideon K. Helegbe; Faiza Tanko; Paul A. Aryee; Setor Aku Lotsu; Mathias J. A. Asaarik; Frank Anaba (Journal of Tropical Medicine)
The Bolgatanga Municipal Health Directorate has reported liver cirrhosis among the first three diseases causing mortality from 2013 to 2015. This implicates hepatitis B virus (HBV) infection considering its high prevalence among blood donors in the Upper East Region of Ghana. However, for a vulnerable group such as market women, there is not much information with regard to the prevalence, knowledge, and attitude towards HBV infection. Thus, this study sought to bridge this gap by determining the seroprevalence, knowledge, and attitude of market women in the Bolgatanga Municipality of Ghana, towards HBV infection. A cross-sectional descriptive study was conducted (from October 2017 to March 2018) among 404 market women using a pretested questionnaire to ascertain the knowledge and attitudes of market women towards HBV infection, while hepatitis B surface Antigen Rapid Diagnostic Test strips were used to screen for the infection. The study revealed that the seroprevalence of hepatitis B among the market women was 15.6%, and majority of the study subjects (>60%) were unaware of HBV infection. Overall, knowledge on and attitude towards HBV infection were low and poor, respectively, with a significantly high number of the market women not wanting infected individuals to be isolated (p=0.049). A high seroprevalence, together with poor attitude and low knowledge levels, as seen in this study is of great public health concern. The study recommends regular HBV screening for market women for prompt treatment and vaccination as well as continuous health education to increase knowledge level and improve the poor attitudes of market women towards HBV infection.